2017
DOI: 10.1111/rda.12921
|View full text |Cite
|
Sign up to set email alerts
|

Dose rates of antimicrobial substances in boar semen preservation—time to establish new protocols

Abstract: To achieve a standardized number of spermatozoa in the final AI dose, varying amounts of extender fluid with a fixed concentration of antimicrobial substances are currently added to boar ejaculates. This practice ignores the different degrees of dilution of the antimicrobials in the end product. In calculating the final concentration of gentamicin in AI doses from 27,538 processed boar ejaculates, we demonstrated varying gentamicin concentrations in the resultant extended boar semen samples. The median concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…This study was pioneering at comparing gentamicin with several other antimicrobials such as ampicillin, apramycin and cefoxitin. Currently, gentamicin has established itself as one of the most used antimicrobials in boar semen diluents (Schulze et al, 2017). However, Gączarzewicz et al (2016) demonstrated that the inhibitory activity of even gentamicin may be limited during long-term preservation (16°C for five days) in diluent (X-cell ® ).…”
Section: Use Of Antibacterial Substances In Semen Extendersmentioning
confidence: 99%
“…This study was pioneering at comparing gentamicin with several other antimicrobials such as ampicillin, apramycin and cefoxitin. Currently, gentamicin has established itself as one of the most used antimicrobials in boar semen diluents (Schulze et al, 2017). However, Gączarzewicz et al (2016) demonstrated that the inhibitory activity of even gentamicin may be limited during long-term preservation (16°C for five days) in diluent (X-cell ® ).…”
Section: Use Of Antibacterial Substances In Semen Extendersmentioning
confidence: 99%
“…One subset was validated individually and the remaining 4 subsets for training in Google's TensorFlow [28]. Three method, dropout [29], data augmentation [30] and early stopping [31], were used to minimize the overfitting risk. Technical details were described in supplementary methods and 7…”
Section: Training Of Cnn Modelsmentioning
confidence: 99%
“…Numerous studies have indicated that the addition of antibacterials to semen extenders is an effective method to inhibit bacterial growth, prolong sperm preservation time in vitro, and increase conception rates (Bresciani et al, ; Yaniz, Marco‐Aguado, Mateos, & Santolaria, ). Common antibiotics included penicillin, streptomycin, and gentamicin (Oplinger & Wagner, ; Schulze et al, ). However, the long‐term use of antibiotics has led to an increase in the drug resistance of certain bacteria and the therapeutic effects of the medicines have been significantly reduced (Speck et al, ).…”
Section: Introductionmentioning
confidence: 99%